2016
DOI: 10.1038/ijo.2016.180
|View full text |Cite
|
Sign up to set email alerts
|

METRNL decreases during adipogenesis and inhibits adipocyte differentiation leading to adipocyte hypertrophy in humans

Abstract: Taken together, the downregulation of METRNL during adipogenesis and functional induction of increased proliferation in SVF cells with concomitant inhibition of adipocyte differentiation may result in hypertrophic AT accumulation. This may also explain our observations of increased METRNL expression in adipocytes but not SVF cells in obese children compared with lean children and the subsequent hyperinsulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
5
32
1
Order By: Relevance
“…Wang et al reported that serum Metrnl levels were increased in overweight and obese subjects when compared with subjects of normal weight, and it was significantly correlated with BMI [7]. Löffler et al also reported increased Metrnl expression in adipocytes in obese children compared with lean children [16]. Our findings contradict data obtained by Wang and Löffler.…”
Section: Discussioncontrasting
confidence: 89%
“…Wang et al reported that serum Metrnl levels were increased in overweight and obese subjects when compared with subjects of normal weight, and it was significantly correlated with BMI [7]. Löffler et al also reported increased Metrnl expression in adipocytes in obese children compared with lean children [16]. Our findings contradict data obtained by Wang and Löffler.…”
Section: Discussioncontrasting
confidence: 89%
“…9) Our previous studies showed that Metrnl is highly expressed in white adipose tissue in both rodents and humans and plays important roles in adipose biology. 3,7) Recently, in line with our animal results, Löffler et al 10) showed that Metrnl expression is higher in subcutaneous adipocytes of obese children when compared with lean children and is associated with adipocyte size.…”
supporting
confidence: 75%
“…However, our results go beyond those of Li et al's study, which showed no significant association of Metrnl with BMI, TC, glucose, or TG in human subjects undergoing a physical examination. Loffler et al reported that Metrnl expression in adipocytes was higher in obese children compared to lean children. The discrepancies in these studies might be due to several potential factors including study design, ethnicity, sample size, patient characteristics, and concomitant disease.…”
Section: Discussionmentioning
confidence: 98%